Sinergi Akuntansi dan Agroteknologi: Pemberdayaan UMKM Ibu Rumah Tangga - Lidona Aprilani, Triana; Nida Utamie, Dara; Sukriati, Sukriati; Amni Rosadi, Narita; Novida, Sari (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2024)
Housewives managing Micro, Small, and Medium Enterprises (MSMEs) in the agricultural sector and agricultural processed products often face challenges in running their businesses, particularly in financial record-keeping and productivity enhancement. Mastery of appropriate accounting technology can help them manage business finances efficiently, while the application of agrotechnology can improve the quality and quantity of production output (Supriyadi, 2020). This community service program aims to integrate accounting technology and agrotechnology for MSMEs managed by housewives in Bintaro Village, South Ampenan District, Mataram City. The methods used in this program include training in financial record-keeping through a simple accounting application and the application of easy-to-adopt agricultural technology suited to local potential. The results of this program show an increase in participants' understanding of managing business finances, as well as improvements in efficiency and productivity in agricultural outputs and processed products. The integration of accounting and agrotechnology is expected to help housewives develop their businesses more independently and sustainably, thereby making a significant contribution to the well-being of their families and surrounding communities.